DEKONSTRUKSI KEKUASAAN DALAM KELUARGA PEKERJA MIGRAN INDONESIA DALAM PERSPEKTIF PETER M. BLAU - Mahardani Febrihapsari; Wiwik Prihartanti; Agus Rahmanto (Journal of Urban Sociology, 2020)
Migration is one of population studies which has been widely reviewed, particularly labor migration between countries. A booming labor movement recently, gives no small contribution for the country through remittances. However, labor migration, women migrant workers in particular, has its own consequences in the form of changes that occur not only at community level but also at family level. This study attempts to portray power in the migrant family after the wife migrates. The approach used in this study was qualitative with the perspective of Peter M Blau Social Exchange. The results of the study reveal that migration done by women migrant workers changes the power in the family, that is power destruction in the form of domination on the final decision in the family. An increase in economy in line with an increase or even a strengthening in bargaining position of women to men in the family. In this level, Economy is the major determinant of the change. Whereas, the knowledge obtained by the women while being overseas is the minor determinant in the social exchange to husband.Keywords: Power Deconstruction, Women Migrant Worker, Bargaining Position